Cognitive Function Before and After Left Heart Catheterization. Issue 6 (10th March 2018) - Scott, David A.; Evered, Lisbeth; Maruff, Paul; MacIsaac, Andrew; Maher, Sarah; Silbert, Brendan S.
Abstract : Background: Hospital procedures have been associated with cognitive change in older patients. This study aimed to document the prevalence of mild cognitive impairment in individuals undergoing left heart catheterization (LHC) before the procedure and the incidence of cognitive decline to 3 months afterwards. Methods and Results: We conducted a prospective, observational, clinical investigation of elderly participants undergoing elective LHC. Cognition was assessed using a battery of written tests and a computerized cognitive battery before the LHC and then at 3 months afterwards. The computerized tests were also administered at 24 hours (or discharge) and 7 days after LHC. A control group of 51 community participants was recruited to calculate cognitive decline using the Reliable Change Index. Of 437 participants, mild cognitive impairment was identified in 226 (51.7%) before the procedure. Computerized tests detected an incidence of cognitive decline of 10.0% at 24 hours and 7.5% at 7 days. At 3 months, written tests detected an incidence of cognitive decline of 13.1% and computerized tests detected an incidence of 8.5%. Cognitive decline at 3 months using written tests was associated with increasing age, whereas computerized tests showed cognitive decline was associated with baseline amnestic mild cognitive impairment, diabetes mellitus, and prior coronary stenting. Conclusions: More than half the patients aged >60 years presenting for LHC have mild cognitive impairment. LHC is followed by cognitive decline in 8% to 13% of individuals at 3 months after the procedure. Subtle cognitive decline both before and after LHC is common and may have important clinical implications. Clinical Trial Registration Information: URL:www.anzctr.org.au . Unique identifier: ACTRN12607000051448.